Promosi Water World Citra Raya Tangerang Berbentuk Iklan Video - Syafnidawati Syafnidawati; Eldy Aufar Mahardhika (UNIVERSITAS RAHARJA, 2019)
Advertising is one of the key elements in the promotion mix, the company has to design its ads so that the communication and promotion objectives can be achieved. Advertisement part of the message in communication, for how to communicate a type of business using the communication process in a verbal or not verbal manner depending on the media used. Business naming Slogan used entertainment information to consumers. The meaning of his farming. The researcher therefore asked two research questions. That is 1) how the advertising efforts, and 2) whether the characteristics of a business advertisements. Based on that, it has a distinct meaning and characteristic of it. Any indirect use that dominates in each ad.